Efl Students' Challenges to Read Online - Nindya Juwita Utimadini (Jurnal Pendidikan Bahasa, 2021)
Reading is one of the most effective skills that develop language learner skill. In this digital era, where most of life activities has transformed to an ease and fast, Reading become daily routine. This routine means that reader interact with many texts online daily. The technology provided many aids for English Language Learner to read. However, this paper aimed to unfold the challenges faced by the English language learner to read in online environment. Therefore, the 30 English Education students of Tarbiyah and Teacher Training of IAIN Pontianak are told to carry out Extensive Reading in online environment. The qualitative study drawn the real and factual challenges faced by the students. The challenges to read in online environment are (1) Difficult to choose interesting material or text to read, (2) Health Issues related to online reading, (3) Unsupportive Facilities, and (4) Difficulty in maintaining focus to the text.